108k views
5 votes
If (x - 1) + (x - 2) + (x - 3) + (x - 4) = x, then what is x?

User KyleUp
by
5.7k points

1 Answer

5 votes

Remove parentheses, cancel x on both sides. Simplify −1+x−2+x−3+x−4 to −10+3x then regroup the terms. Finally, add 10 to both sides and divide both sides by 3.

(x - 1) + (x - 2) + (x - 3) + (x - 4) = x

x−1+x−2+x−3+x−4=x

−1+x−2+x−3+x−4=0

−10+3x=0

3x−10=0

3x=10

x=10/3

Hope this helps, HAVE A BLESSED AND WONDERFUL DAY! As well as a great Superbowl Weekend! :-)

- Cutiepatutie ☺❀❤

User Leonardus Chen
by
5.9k points